"Engrave this memory in your heart as if on a tablet...": Memory, meditation, and visual imagery in seventeenth-century Ukrainian preaching. Issue 2 (2nd April 2020) - Bartolini, Maria Grazia
ABSTRACT: Much has been written on the importance of the arts of memory since Frances Yates's The Art of Memory (1966). However, in the expanding body of scholarship on mnemonic practices in the Middle Ages and early modern period, little attention has been given to the relationship between memory, preaching, and devotion, and to how sermons were remembered and transmitted. This article sets out to fill this gap by exploring the connection between rhetorical invention, memory, and the visual image in seventeenth-century Ukrainian preaching. Using the printed sermon collections of Ioanykii Galiatovs'kyi ( Kliuch Razuminiia, 1659) and Antonii Radyvylovs'kyi ( Ohorodok Marii Bohorodytsy, 1676; Vinets Khrystov, 1688) and the previously unstudied manuscript vernacular sermons of Stefan Iavors'kyi (1690s), the author demonstrates how Ukrainian Orthodox literati understood the role that visual perception, imagination, and memory played in structuring their own rhetorical material as well as developing their listeners' virtuous behaviour. In particular, she argues that sermon literature used the techniques of visualization and memorization that enhanced the ability to meditate privately, and that these texts' emphasis on vividness ( enargeia or hypotyposis ) and memory schemes was strengthened by the Aristotelian idea that all thoughts and feelings depended on the imagination.